1998
DOI: 10.1074/jbc.273.10.5655
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Dimeric Structure in Cu,Zn Superoxide Dismutase

Abstract: To investigate the structural/functional role of the dimeric structure in Cu,Zn superoxide dismutases, we have studied the stability to a variety of agents of the Escherichia coli enzyme, the only monomeric variant of this class so far isolated. Differential scanning calorimetry of the native enzyme showed the presence of two well defined peaks identified as the metal free and holoprotein. Unlike dimeric Cu,Zn superoxide dismutases, the unfolding of the monomeric enzyme was found to be highly reversible, a beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…The monomer intermediate is common to the aggregation of both wild type and fALS-associated mutant SODs. Because the dimeric structure is necessary for proper enzymatic action and stability (33,34), this may account for higher levels of oxidative stress in ALS patients (14) and reports of decreased enzymatic activity in some fALS SOD1 mutants (35). We found that monomerization and aggregation results from the oxidative modification of relatively few residues that are removed from the dimer interface of SOD1.…”
Section: Wild Type Sod1 Is Aggregation-prone Under Oxidativementioning
confidence: 84%
“…The monomer intermediate is common to the aggregation of both wild type and fALS-associated mutant SODs. Because the dimeric structure is necessary for proper enzymatic action and stability (33,34), this may account for higher levels of oxidative stress in ALS patients (14) and reports of decreased enzymatic activity in some fALS SOD1 mutants (35). We found that monomerization and aggregation results from the oxidative modification of relatively few residues that are removed from the dimer interface of SOD1.…”
Section: Wild Type Sod1 Is Aggregation-prone Under Oxidativementioning
confidence: 84%
“…Bacterial Cu,Zn-SODs easily lose their metal cofactors and are therefore irreversibly inactivated in the presence of EDTA (30,49). The observed rates of EDTA-mediated inactivation vary for different enzymes (30), are affected by the stability of the quaternary structure (43,49), and are strongly influenced by pH, being faster at alkaline pH (29,30).…”
Section: Contributions Of Sodci and Sodcii To Salmonellamentioning
confidence: 99%
“…SodCI has a very high affinity for copper ions and cannot be completely demetallated by the procedures previously described to obtain apoSODs lacking both copper and zinc ions (30,43). Therefore, to remove the copper, the two StSOD enzymes were treated with potassium ferrocyanide to reduce the metal, then dialyzed for 12 h against 100 mM potassium phosphate buffer, 50 mM KCN, pH 6.0 (44).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations